Low Temperature Synthesis of High Energy Facets Exposed Sheet–like Anatase TiO2 Mesocrystals Show Reduced e−/h+ Pair Recombination Rates and Enhanced Photoactivity. Issue 19 (29th November 2016) - Sumina, N. B.; Kumar, S. Nishanth; Achu, R.; Kumar, B. S. Dileep; Ray, Alok K; Warrier, K. G. K.; Pillai, Saju
Abstract: Herein, we report low temperature synthesis of anatase TiO2 mesocrystals with {001} facets exposed sheet‐like morphology via fluorine‐free synthesis by the synergistic effect of microwave and ultrasound treatments. The synthesized TiO2 powder showed higher surface area and enhanced photocatalytic degradation of a model dye under white light irradiation. The sheet‐like anatase TiO2 mesocrystals resulted long‐lived charge carriers and separation that was confirmed from photoluminescence and photocurrent measurements. A five‐fold enhancement in the photocurrent was obtained for the mesocrystals compared to reference sample, which revealed that the orientation of nanocrystallites in sheet‐like morphology play a pivotal role in electron transport. The effect of charge carriers on photocatalytic activity was studied in detail and it followed the order, hydroxyl radicals> holes>electrons. Additionally, the TiO2 sol showed excellent stability. Further, the photoinactivation of Escherichia coli and Candida albicans was evaluated using zone of inhibition test under indoor irradiation and synthesized anatase TiO2 showed a clear zone of inhibition with diameter 37.2 mm and 40.0 mm, respectively whereas commercial TiO2 shows meager inactivation. The results indicate that our approach of combined microwave and sonication can serve as a facile approach for the synthesis of {001} facets exposed anatase sheet‐like TiO2 mesocrystals under halide‐free and low temperature conditions. Abstract : We report a low temperature and fluorine‐free synthesis of anatase TiO2 with sheet‐like morphology is having exposed {001} facet that resulted in enhanced photocatalytic and biocidal activities.